Reconstructing past fisheries catches for large pelagic species in the Indian Ocean - Heidrich, Kristina N.; Meeuwig, Jessica J.; Zeller, Dirk (Frontiers in Marine Science, 2023)
Comprehensive catch data are fundamental to support the sustainable management of large pelagic fisheries. However, catch data reported by the Indian Ocean Tuna Commission (IOTC) on behalf of its member countries currently under-represent the extent of these fisheries in the Indian Ocean. We reconstructed fisheries catches of large pelagic species for the Indian Ocean from 1950 to 2020, aiming to improve the comprehensiveness of existing reported data and to provide more ecologically relevant datasets for research and management uses. We reconstructed catches for 42 countries operating five major gear groups (longline, purse seine, gillnet, pole-and-line, and other gears) in the large pelagic fisheries. Reconstructed catches were 30% higher than the data reported by the IOTC. We demonstrated that distant-water fishing fleets historically dominated large-scale industrial fishing but were gradually replaced by fleets flagged to Indian Ocean rim countries. Our results also indicated an average discard rate of ~14% over the 1950-2020 period, primarily attributable to extensive discarding practices associated with longline and gillnet vessels. Reporting over time has improved only for tunas, whereas shark catches still remain under-reported, accounting for 51% of total unreported landings and discards in 2020. We confirmed substantial taxonomic aggregation in the data reported by the IOTC on behalf of its member countries, masking important patterns and trends and further complicating the sustainable management of exploited species in the Indian Ocean. We recommend substantially increased observer coverage and far better and stronger support by all member countries to improve the fisheries statistics in the IOTC.